Teaching readers of English [ students, texts, and contexts - Hedgcock, John; Ferris, Dana (Routledge, 2009)
Suitable for pre and in-service ESL and EFL educators, this title balances insights from the reading theory and research with practical, and field-tested strategies for teaching and assessing L2 reading in secondary and post-secondary contexts. It provides a survey of L2 reading theory and research